Total laparoscopic hysterectomy: Analysis of the surgical learning curve in benign conditions - Terzi, Hasan; Biler, Alper; Demirtas, Omer; Guler, Omer Tolga; Peker, Nuri; Kale, Ahmet (ELSEVIER, 2016)
Objective: To assess the learning curve for total laparoscopic hysterectomy. Methods: This study was a retrospective analysis of the learning curve for two surgeons during their first 257 consecutive cases of total laparoscopic hysterectomy at a teaching hospital. Patients were divided sequentially into groups comprising the first 75 patients, the next 75, and the final 107 patients. Age, body mass index, gestational parity, indications for laparoscopic hysterectomy, previous pelvic surgery, operating time, haemoglobin decline, complications, need for transfusion, and length of hospital stay were evaluated. Results: The mean operating time for total laparoscopic hysterectomy reduced significantly from 76.2 min to 68.9 min (p = 0.001) between the first and second 75-patient groups. Linear regression analysis showed a plateau was reached on the learning curve after 71-80 cases. The rate of all complications started at 8\% in the first group of 75 patients, reduced to 6.7\% in the next group, and decreased further in the final group to 4.7\%. The decline was not statistically significant (p = 0.6). The difference in the need for transfusion was statistically significant between the first 75 patients and the second group of 75 (p = 0.04). Conversion from laparoscopy to laparotomy was required in five patients, four in the early group and one in the final group. Age, body mass index, parity, previous pelvic surgery, decline in haemoglobin, and length of hospital stay were similar among the three groups. Conclusions: A plateau in the learning curve for TLH was reached after the first 75 cases. We can infer that there is a learning curve for TLH as confirmed by the decrease in operating time (accompanied by no change in complications) correlated to gain in experience. On the other hand, one should not disregard the fact that laparoscopy is not a complication-free surgery and achievement of the learning curve does not exclude complications. Gynaecological surgeons can perform TLH securely during the learning curve. (C) 2016 IJS Publishing Group Ltd. Published by Elsevier Ltd. All rights reserved.
Keywords: Laparoscopic hysterectomy; Total laparoscopic hysterectomy; Learning curve